Teachers' Implementation of Authentic Speaking Assessment: A Case Study of Senior High Schools in Ambon - Firdausi, Wirdah (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2024)
The present study investigates authentic assessment practices in speaking lessons at senior high schools in Ambon city, Indonesia. Using a qualitative descriptive approach, the research examined the types of authentic assessment tasks implemented by English as a Foreign Language (EFL) teachers and their perceptions regarding implementation. Data were collected through questionnaires, semi-structured interviews, and document analysis from seven experienced English teachers across three public senior high schools: SMA Negeri 2 Ambon, SMA Negeri 3 Ambon, and SMA Negeri 5 Ambon. The study employed Miles and Huberman's interactive model for data analysis, encompassing data reduction, data display, and conclusion drawing. Findings revealed that teachers utilized eight distinct authentic assessment tasks: oral interviews, picture-cued descriptions, video clips, information gaps, story/text retelling, role plays, oral reports, and debates. Role-play emerged as the most frequently implemented task, with all participating teachers incorporating it into their speaking assessments. Teachers demonstrated positive perceptions toward authentic assessment, acknowledging its benefits in enhancing student motivation, developing practical skills, and improving learning outcomes. However, implementation challenges persisted, including time constraints with large classes, resource limitations, varying student proficiency levels, and assessment complexity. Recommendations emphasize the need for targeted professional development in authentic assessment methodology, institutional support for resource allocation, and strategic approaches to overcome implementation challenges. This study contributes to the understanding of authentic assessment practices in EFL contexts and provides practical insights for educational stakeholders seeking to enhance speaking assessment methods.